GAS SENSING PROPERTIES OF RUTILE-TiO2 (100) FILMS PREPARED BY PULSED LASER DEPOSITION - Bambang Siswanto; Shunya Yamamoto; Masahito Yoshikawa (GANENDRA Majalah IPTEK Nuklir, 2008)
gas sensing property of TiO2 thin films have been demonstrated in rutile-TiO2 (100) films grown on the a-Al2O3 (0001)substrates by Pulsed Laser Deposition (PLD). High quality rutile-TiO2 (100) films were successfully grown on a-Al2O3(0001) with the substrate temperature at 500oC under 15 mTorr of O2 gas pressure. The thickness and crystallinity ofTiO2 films were evaluated by Rutherford backscattering spectrometry combined with channeling (RBS/C) and X-raydiffraction using q-2q scans. To evaluate CO2 gas sensing property of TiO2 films, the dependence of the changing ofelectrical resistivity on the temperature was measured. It’s found that high crystallinity rutile-TiO2 (100) films on the a-Al2O3 (0001) substrate kept at 100oC exhibits good gas sensing property for CO2 gas.Keywords: X-ray diffraction, laser epitaxial, TiO2 thin film, electrical resistivity, CO2